Whaling will never do for me : the American whaleman in the nineteenth century - Busch, Briton Cooper (University Press of Kentucky, 2009)
""I just begin to find out that whaling will never do for me and have determined to leave the ship here if possible."" That sentiment, expressed by a foremast hand aboard the ship Caroline in 1843, is one shared by many of the whalemen in this fascinating book. Interest in Herman Melville's Moby Dick has contributed to a substantial literature on the history and lore of the industry. But not until now has the vast body of surviving whaleship logs and journals been used to paint an encompassing picture of the difficult but colorful life aboard nineteenth-century American whaling vessels. Briton